Taxonomic revision of the genus Anostomoides (Characiformes: Anostomidae) - Assega, Fernando Massayuki; Birindelli, José Luís Olivan (Zootaxa, 2019)
A taxonomic revision of Anostomoides is herein presented based on a comprehensive revision of specimens deposited in fish collections and the literature. The present revision proposes that A. laticeps is a junior synonym of A. atrianalis, while A. passionis is a junior synonym of Leporinus nattereri, and the latter is thus transferred to Anostomoides, forming the new combination Anostomoides nattereri. Principal Components Analysis (PCA) showed that examined specimens form two distinct morphotypes, corroborating the validity of both A. atrianalis and A. nattereri. Anostomoides nattereri is distinguished from A. atrianalis by having four branchiostegal rays (vs. three), three pores in infraorbital one (vs. four), 37–39 pored lateral-line scales (vs. 41–44), lower lip with rounded dermal papillae (vs. forming ridges), three dark  rounded midlateral blotches (vs. three or four vertically elongated blotches and/or a faded dark longitudinal stripe), dark lines between scale series on posterior half of body on specimens smaller than 150 mm SL (vs. dark lines absent), a greater body depth (27.6–36.2 % vs. 24.5–38.7% of SL) and smaller interorbital distance (34.4–53.8 % vs. 42.6–67.3 % of HL). Anostomoides nattereri is distributed across several tributaries of the Amazon and Orinoco rivers, whereas A. atrianalis is widespread throughout the Amazon, Orinoco, and Essequibo basins. The genus Anostomoides is currently diagnosed based on a combination of non-exclusive characters: upturned or slightly upturned mouth with four premaxillary teeth including symphyseal tooth bicuspid or with blunt cutting edge, remaining teeth slightly tricuspid (with medial cuspid distinctly larger); four dentary teeth, symphyseal tooth with truncate cutting edge (without cusps); second tooth with a single large cusp, and two lateral teeth with three or slightly more small cusps.